T024 Modulation of gamma oscillations dynamics by weak electric fields - Reato, D.; Bikson, M.; Parra, L. (Clinical neurophysiology, 2017)
We are interested in the acute effects of weak electric fields on gamma oscillations, which is a critical neural substrate of information processing in the hippocampus. Stimulation with weak currents is known to have a relatively small effect on the firing of individual neurons. Yet, when applying stimulation during gamma activity in rodent slices, we find that the effects of fields are significantly amplified by the neuronal network. Using a computational model we demonstrate that this amplification is the result of the dynamic push and pull of the excitatory/inhibitory feedback loop, which is the hallmark of gamma oscillations. The recorded effects have a mixed spatial distribution in CA3, which is the hippocampal region with the strongest recursive feedback and the main generator of gamma activity. This recursive structure is sometimes thought to be the core processing unit for associative memories. Interestingly, when applying constant current stimulation, the enhancement of gamma activity and neuronal firing outlast the period of stimulation by several minutes, suggesting plastic effects of DC stimulation on this important associative neuronal network.